Evaluating the impact of peer coaching through teachers' teaching principles - Lei, Kai Cheong (2016)
The English language programme of the Macau University of Science and Technology (MUST) has a pressing need for a continuing professional development (CPD) programme. Peer coaching is identified as the type of CPD that is potentially suitable for the English programme. It also serves as a catalyst for building a learning community. The main purpose of this study is to examine the impact of a peer coaching programme on the teachers’ beliefs and practice. To do so, I investigate the difference in teachers’ teaching principles (please see Section 5 of Chapter 2 for details) in direct relation to their actual classroom practice before and after the peer coaching programme in one school term. By comparing how the teachers make sense of their actual classroom practices before and after the programme, this study can address the impact of the peer coaching programme on the teachers’ theories-in-use and has important implications for understanding and improving teaching. This study also attempts to investigate to what extent peer coaching helps to build a learning community.